Chatter detection on thin wall machining of alluminum alloy under MQL condition - Amirul Syafiq, Ibrahim (2016)
The purpose of this project was to analyze and study the chatter detection on thin wall machining of aluminum alloy under mql condition. Initially, 3 difference type of thin wall design are selected which is L shape, T shape and Pocket shape, then the chatter phenomenon during the cutting experiment were observed by using the accelerometer with a variable value of depth of cut. Three types of chatter detection method are applying in this experiment to achieve the accurate result which is by acceleration, time domain and surface roughness test. From the results, it was clear that the parameter depth of cut and the design of the thin wall manipulate the occurring of chatter or non-chatter in the machining process.